Prevalence and factors influencing anaemia among urban adolescent females, a cross sectional study - Poyyamozhi, J. S.; Rushender, Rajan; Murali Mohan Reddy, G. (International Journal Of Community Medicine And Public Health, 2018)
Background: Despite many organized efforts by the government, adolescent anemia remains to be a major public health problem in India. The prevalence of anemia and factors influencing it in urban adolescent females is a relatively less studied aspect. Hence the current study is conducted with an objective of assessing the prevalence and factors influencing anemia among adolescent school girls living in an urban locality. Methods: The current study was a community-based cross sectional study conducted in the selected schools and colleges of Permabalur town, south India, in the field practice area of Dhanalakshmi Srinivasan Medical College and Hospital between June to December 2017. Total 373 adolescent girls selected by multistage simple random sampling were included in the study. The hemoglobin was assessed by cyanmethemoglobin method. Results: The prevalence of anaemia among urban adolescent girls was 41.1% (95% CI 0.36-0.46). The proportion of mild and moderate anaemia was 37% and 4.10% respectively and none had severe anaemia. Compared to upper middle class, the odds of anemia were 14.16 times more in the lower class (95% CI 4.54-44.12, p<0.001). Compared to scanty/normal bleeding, the odds of anemia were 2.943 (95% CI 1.4-3.87 p<0.05) more in girls with heavy bleeding. Age, upper lower or lower middle socio-economic strata, religion, type of family and menstrual irregularity did not have any statistically significant association with anemia. Conclusions: Anemia is highly prevalent among adolescent girls and there is a need to intensify efforts all levels to reduce the prevalence of anemia.